2016
DOI: 10.1159/000447603
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors for Refractory Fistula after Esophagectomy with Gastric Tube Reconstruction in Patients with Esophageal Cancer

Abstract: Background/Aims: Anastomotic leakage (AL) after esophagectomy is associated with high rates of postoperative morbidity and mortality. In cases with leakage, a refractory fistula (RF) is sometimes recognized after esophagectomy. The aim of this study was to evaluate the risk factors for RF after esophagectomy with gastric tube reconstruction. Methods: This study enrolled 244 consecutive esophageal cancer patients who had undergone esophagectomy with gastric tube reconstruction. RF was defined as a noncurative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
9
2
Order By: Relevance
“…In addition, clinical outcomes in the present series seemed very satisfactory, in that persistent post-esophagectomy fistula, refractory to conservative treatment, resolved within a relatively short period in 10 patients. Yamana et al reported that the mean period from first operation to resumption of oral intake in patients with persistent fistula after esophagectomy was 151.3 days, in stark contrast to the 65.3 days in the present series [10]. The mean periods from the first and final application of the PGAfibrin method to the resumption of oral intake were 31.6 and 14.7 days, respectively, notably shorter times compared to previous reports.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In addition, clinical outcomes in the present series seemed very satisfactory, in that persistent post-esophagectomy fistula, refractory to conservative treatment, resolved within a relatively short period in 10 patients. Yamana et al reported that the mean period from first operation to resumption of oral intake in patients with persistent fistula after esophagectomy was 151.3 days, in stark contrast to the 65.3 days in the present series [10]. The mean periods from the first and final application of the PGAfibrin method to the resumption of oral intake were 31.6 and 14.7 days, respectively, notably shorter times compared to previous reports.…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, clinical outcomes in the present series seemed very satisfactory, in that 10 patients with the PFACTAL after esophagectomy achieved cure within a relatively short period. Yamana et al reported that the mean period from first operation to resumption of oral intake in patients with the PFACTAL after esophagectomy was 151.3 days, in stark contrast to the 65.3 days in the present series [10].…”
Section: Accepted M Manuscriptcontrasting
confidence: 83%
“…Anastomotic stenosis and fistula are the most common postoperative complications of esophageal cancer (18). These two complications not only lead to a low quality of life of patients but also endanger their lives (19). Therefore, it is extremely important to reduce the risk factors of anastomotic stenosis and fistula, and it is particularly urgent to find new embedding materials.…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al [17] mentioned that there were no significant differences in survival between the preoperative chemoradiotherapy and postoperative chemoradiotherapy arm (p > 0.05). However, the postoperative therapy also provides several benefits including decision based on true pathologic stage, more accurate assessment of disease extent to allow for delineation of disease involvement, and less concern about increase in perioperative morbidity and mortality after preoperative induction [4,5,18]. Although CCRT is an important component of therapy, when used alone, it results in unacceptably high rates of relapse and poor long-term survival rates in LN-positive patients.…”
Section: Discussionmentioning
confidence: 99%